التباين الاجتماعي في العصر الحجري الحديث بمنطقة النيل الأوسط - السيد، ريهام محمود زكي; عبدالمجيد، زكريا رجب; فرج، حندوقة إبراهيم (جامعة القاهرة - معهد البحوث والدراسات الافريقية, 2022)
لقد أمدتنا أعمال البحث العلمي، والحفائر بصورة شبه واضحة عن الحياة السابقة خلال عصور ما قبل التاريخ، لا سيما العصر الحجري الحديث بمنطقة النيل الأوسط والتي يقصد بها وادي النيل والمنطقة فيما حوله بين الجندل الأول شمالا، والجندل السادس جنوبا عند ملتقى النيلين الأبيض والأزرق عند الخرطوم. وهي ذلك تضم 3 مناطق رئيسية: النوبة السفلى، النوبة العليا، وسط السودان. وقد ركزت معظم الأعمال العلمية على دراسة الجبانات بمنطقتي النوبة العليا (كمواقع: البرقة، كدركة، R 12)، ووسط السودان (مثل مواقع: الكدرو، الغابة، الكدادة) حيث تمت دراسة البقايا الآدمية، والمواد الثقافية المصاحبة للدفنات (الأثاث الجنائزي). ومن خلال الدراسة المفصلة، يظهر لنا العديد من الجوانب الهامة لا تقتصر فقط على الحياة الجنائزية وعادات الدفن، ولكن أيضا الجانبين الاقتصادي والاجتماعي. تلقى هذه الورقة البحثية الضوء على بعض الجوانب المتعلقة بالتباين الاجتماعي بمنطقة النيل الأوسط من خلال تحليل ودراسة الأثاث الجنائزي سواء العدد أو الكمية أو المواد المستخدمة لصناعته (محلية –مستوردة)، كمحاولة لإيضاح الجوانب المختلفة للمجتمع النيوليثي بمنطقة النيل الأوسط. Throughout the archaeological research in the Middle Nile Region (the area from the first cataract north to the sixth cataract south where the blue and White Nile are connected), a better understanding of the human past life during Neolithic can be established. Middle Nile Region includes three important culture areas: Lower Nubia, Upper Nubia and Central Sudan. Most of the archaeological research is focused mainly on cemeteries in Upper Nubia (El- Barga, R12 and Kadruka) and Central Sudan (Kadero I, Ghaba and Kadada). In addition to the excavation of the Neolithic burials with the detailed study of both burials, cultural materials and the funeral goods that accompanied the deceased. The archaeological research also converges the re-examination of the cultural materials (mainly funeral goods) from the previous projects that were initiated earlier. The analysis of these data identifies remarkable results about Neolithic past life, not only the funeral aspect but also the socio economic aspect of these communities. The current research aims to highlight various aspects of the social differentiation in Neolithic communities in the Middle Nile Region based on analyzing the distribution of the funeral goods in burials according to their quantity, quality, and materials, in addition to other important elements that reflect the notable status of certain burials such as special treatment and/or spatial distribution of burials in the cemetery. Furthermore, to emphasize the possible contact between these communities by highlighting some common features or behaviors.
Keywords: العادات الاجتماعية -- العادات الجنائزية -- التباين الاجتماعي -- التاريخ القديم